The gold particles - Yahya, Mohamad Ridzuan; Mohamad, Rosfarizan (Universiti Putra Malaysia Press, 2017)
Light scattering techniques are widely used for determination of metal nanoparticle size. Metal nanoparticles are finding increasing application in the preparation of new nanocrystalline materials, with metal oxide composites being used to confer new electronic, magnetic, and optical properties into material structures.